1984
DOI: 10.1038/bjc.1984.237
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial cancer following treatment for breast cancer: A case-control study in Denmark

Abstract: Summary To evaluate the risk of endometrial cancer subsequent to breast cancer, a case-control study was carried out in Denmark. Between 1943Between -1977 (Schoenberg, 1977;Kelsey & Hildreth, 1983). This may reflect a common aetiology of the two cancers (Armstrong, 1979) as well as the influence of various treatments for breast cancer (Hoover et al., 1976

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The height effect that we observed in women aged 60 or older is difficult to interpret, since it was limited to this age group and was in most part explained by the association with weight. Most past studies of this cancer have found no association with height (Blitzer et al, 1976;Elwood et al, 1977;Ewertz et al, 1984;Albanes et al, 1988).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The height effect that we observed in women aged 60 or older is difficult to interpret, since it was limited to this age group and was in most part explained by the association with weight. Most past studies of this cancer have found no association with height (Blitzer et al, 1976;Elwood et al, 1977;Ewertz et al, 1984;Albanes et al, 1988).…”
Section: Discussionmentioning
confidence: 95%
“…There is now persuasive evidence that body weight is associated with post-menopausal endometrial cancer (Wynder et al, 1966;Blitzer et al, 1976;Elwood et al, 1977;Lew and Garfinkel, 1979;Kelsey et al, 1982;Henderson et al, 1983;La Vecchia et al, 1984;Ewertz et al, 1984;Lawrence et al, 1987;Koumantaki et al, 1989;Folsom et al, 1989). This association has been attributed to the increased levels of biologically active estrogens in obese post-menopausal women (Siiteri, 1978).…”
mentioning
confidence: 99%
“…In endometrial cancer, on the other hand, a causal relationship with certain characteristics of the reproductive history (Ewertz et al, 1984;Kelsey & Hildreth, 1983;Pettersson et al, 1986) excess endogenous oestrogens (Henderson et al, 1982) and with oestrogen therapy (Ewertz et al, 1984;Persson et al, 1986;Zeil, 1982) seems to be more firmly established. We have recently found that the relation between a long menstruation span -defined as the period between menarche and menopause, adjusted for anovulatory periods during parity and lactation -and an increased risk of endometrial cancer is negatively correlated with age at diagnosis (Pettersson et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal treatment has been used for palliation only in advanced cases with too short survival time for an oestrogen induced endometrial cancer to develop. A confounding effect of radiation to the pelvic area or of oestrogen treatment is therefore unlikely (Ewertz et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…We considered as second invasive cancer events loco‐regional invasive recurrences, distant recurrences (metastases) or a second invasive cancer of any primary sites up to December 2011. All cancer events diagnosed within a same three‐month period were considered as synchronous events …”
Section: Methodsmentioning
confidence: 99%